A Study of Biomedical Instrumentation Equipment and Telemedicine Integration - Ghosh, Robin (Journal of Research in Science and Engineering, 2025)
Biomedical Engineering involves developing new devices and procedures that solve medical and health-related problems by combining advanced technologies like Artificial Intelligence and Machine Learning to improve the human health. Bioengineers developing electrical circuits and software’s for Biomedical Instrumentation. In Biomedical Instrumentation equipments are some may be used for recording such as ECG, EEG, EMG and ERG. Some may be used for critical care patients such as pacemakers, defibrillators and ventilators. Some equipments are used to diagnose defect in human body such as X-ray, CT scan, MRI. Advantages of telemedicine in COVID are also reviewed in this paper.